The spatially informed mFISHseq assay resolves biomarker discordance and predicts treatment response in breast cancer - Evan D. Paul; Barbora Huraiová; Natália Valková; Natalia Matyasovska; Daniela Gábrišová; Soňa Gubová; Helena Ignačáková; Tomáš Ondris; Michal Gala; Liliane Barroso; Silvia Bendíková; Jarmila Bíla; et al. (Nature Communications)
Abstract Current assays fail to address breast cancer’s complex biology and accurately predict treatment response. On a retrospective cohort of 1082 female breast tissues, we develop and validate mFISHseq, which integrates multiplexed RNA fluorescent in situ hybridization with RNA-sequencing, guided by laser capture microdissection. This technique ensures tumor purity, unbiased whole transcriptome profiling, and explicitly quantifies intratumoral heterogeneity. Here we show mFISHseq has 93% accuracy compared to immunohistochemistry. Our consensus subtyping and risk groups mitigate single sample discordance, provide early and late prognostic information, and identify high risk patients with enriched immune signatures, which predict response to neoadjuvant immunotherapy in the multicenter, phase II, prospective I-SPY2 trial. We identify putative antibody-drug conjugate (ADC)-responsive patients, as evidenced by a 19-feature T-DM1 classifier, validated on I-SPY2. Deploying mFISHseq as a research-use only test on 48 patients demonstrates clinical feasibility, revealing insights into the efficacy of targeted therapies, like CDK4/6 inhibitors, immunotherapies, and ADCs.